Weakly Covering Spaces in Coc-open Sets (European Journal of Pure and Applied Mathematics, 2022)
In this paper, we define several types of weakly covering spaces concerning coc-open sets, we study some implications between these weakly covering spaces. Also, we give several product theorems under coc-almost open function.
Keywords: Coc-weakly-compact; coc-almost-compact; coc-nearly-compact; coc- R-compact